Associations between training load and acceleration-speed profile in youth soccer athletes - Cardoso, P.; Tavares, F.; Loureiro, N.; Ferreira, R.; Araújo, J.; Reis, J.; Vaz, J. (International Journal of Sports Medicine, 2025)
Soccer requires athletes to exhibit high levels of acceleration and speed, both of which are crucial for optimal performance. The acceleration-speed (A-S) profile is increasingly utilized to assess these sprinting capacities in soccer, providing in situ insights into an athlete`s maximal theoretical acceleration (A0) and speed (S0). This study aimed to investigate the association of external load metrics with A0 and S0 across different age groups in elite academy soccer athletes. One hundred thirty-six athletes, ranging from under-14 to B-team, participated in the study. Training sessions and matches were monitored over a season using Global Navigation Satellite System (GNSS) technology to collect data on the A-S profile and external load metrics. Stepwise regression analysis revealed a positive correlation, in several age groups (under-15, -17, -19, and -23 and B-team), between accumulation of sprint distance (Spr. Dist.) and an increased S0 (R 2: 0.30-0.52). However, no significant correlation was found between any external load metric and A0. These findings highlight the necessity of individualized training interventions and the inclusion of Spr. Dist. throughout the planning of the training load of young soccer athletes for the improvement of sprint capacity. It may also suggest that acceleration in youth soccer athletes may be influenced by other factors, such as strength training.